A Dual NMR Probe Approach to Understanding the Electronic Properties of N‐Heterocyclic Carbenes. Issue 8 (25th June 2021) - Barnett, Christopher; Cole, Marcus L.; Harper, Jason B.
Abstract: The electronic properties of a series of imidazolium‐derived N ‐heterocyclic carbenes systematically substituted at the 4, 5‐positions were investigated through NMR analysis of their palladium and selenone derivatives. This combined approach provided information on both the σ ‐donating ability and the π ‐accepting ability of the carbenes, allowing correlation with the electronic nature of the substituents on the carbene and providing an understanding of the structural features that affect these properties; in principle, this allows design of related ligands with known electronic parameters. Along with a greater understanding of the electronic properties of this series of carbenes, the work allows a comparison of the utility of both NMR probes based on the information gained, and the differences in requirements for preparation and acquisition. With this in mind, the selenone probe is proposed as being able to provide a wide range of electronic information, along with being relatively easily prepared. Abstract : Two probes, or not two probes. That is the question . The electronic ( σ,   π ) characteristics of a range of imidazolium‐based NHCs were probed using NMR analysis of their selenium and palladium complexes.